The Effects Of Physical Activity On Obesity Among The Population Of Different Ages: A Systematic Review - Mima Stankovic; Stefan Djodjevic; Miljan Hadzovic; Dusan Djordjevic; Borko Katanic (University of Montenegro, Faculty for Sport and Physical Education, Montenegrin Sports Academy, 2021)
The aim of this research is a systematic review of the available literature with the effects of physical activity (aerobic training, strength endurance training, etc.) on the obesity of the population of different ages. For collection of previous research on the impact of physical activity on motor fitness, the following electronic databases were searched: PubMed, SCIndeks, PEDro, J-GATE, SCIndes, DOAJ and Google Scholar. The works in the period from 2000 to 2019 were searched. The following keywords were used in the database search: exercise, physical activity, children, adult, aerobic training, resistance training, walking. This systematic review was conducted in agreement with the PRISMA guidelines. The results of the analyzed works indicated that only 20 works met the set selection criteria. In the analyzed works were 845 respondents. In the most researches, the training program lasted 12 weeks, while the shortest program lasted only 5 weeks. Combining endurance training with aerobic training has been shown as the most effective method in the prevention and treatment of obesity.